Dancing with the Carts: UW-Stout Library to Make Noise at Homecoming Parade - Espe, Troy (Volume One magazine, 2016)
The University of Wisconsin-Stout library formed a book cart drill team to perform in the homecoming parade Oct. 8, 2016.
Keywords: book cart drill team; library